The Transformational Leadership of School Administrators under the Jurisdiction of the Office of Vocational Education Commission in Bangkok Metropolis as Perceived by Administrators and Teachers - ออไอศูรย์ กิตติธัช (Journal of Vocational Education in Agriculture, 2019)
The purposes of this study were (1) to study the level of transformational leadership behaviors of administrators in schools as perceived by administrators and teachers. (2) to compare the mean level of transformational leadership behaviors of administrators in schools as perceived by administrators and teachers. According to research, the framework used was based on Bass & Avolio’s concept of transformational leadership behaviors including 4 parts. There were 321 samples including 21 administrators and 300 teachers under Office of the Vocational Education Commission in Bangkok. A questionnaire with 40 questions, five-point Likert scale at the reliability of 0.99, was used for data collection. The data were analyzed using percentage, mean, standard deviation, and T-test for comparing of two groups. The results showed that 1) Idealized Influence was at the highest level (xˉ 1 = 4.60, S.D. = 0.33) 2) Inspirational Motivation was at the highest level (xˉ 1 = 4.57, S.D. = 0.41) 3) Individualized Consideration was at high level (xˉ 1 = 4.48, S.D. = 0.56) and 4) Intellectual Stimulation was at the highest level (xˉ 1 = 4.55, S.D. = 0.41). Furthermore, the result of the level of all sub-scale transformational leadership between administrators and teachers expressed a statistically significantly difference at .05. All sections of the administrators had perceived transformational leadership better than all sections of teachers.